2-(4-Methoxyphenyl)-4,5-dihydro-1H-imidazole - Reza Kia; Hoong-Kun Fun; Hadi Kargar (Acta Crystallographica Section E, 2009)
In the title molecule, C10H12N2O, the dihedral angle between the benzene and imidazole rings is 14.86 (16)°. The approximately planar arrangement of the molecule results in a distance of 2.54 Å between an ortho-H atom of the benzene ring and the double-bonded N atom of the imidazole ring. In the crystal structure, symmetry-related molecules are linked by intermolecular N—H...N hydrogen bonds into one-dimensional chains extending along the a axis.